Trio Clinical Exome Sequencing in a Patient With Multicentric Carpotarsal Osteolysis Syndrome: First Case Report in the Balkans - Stajkovska, Aleksandra; Mehandziska, Sanja; Stavrevska, Margarita; Jakovleva, Kristina; Nikchevska, Natasha; Mitrev, Zan; Kungulovski, Ivan; Zafiroski, Gjorgje; Tasic, Velibor; Kungulovski, Goran (Frontiers in Genetics, 2018)
Exome sequencing can interrogate thousands of genes simultaneously and it is becoming a first line diagnostic tool in genomic medicine. Herein, we applied trio clinical exome sequencing in a patient presenting with undiagnosed skeletal disorder, minor facial abnormalities, and kidney hypoplasia; her parents were asymptomatic. Testing the proband and her parents led to the identification of a de novo mutation c.188C>T (p.Pro63Leu) in the MAFB gene, which is known to cause multicentric carpotarsal osteolysis syndrome (MCTO). The c.188C>T mutation lies in a hotspot amino acid stretch within the transactivation domain of MAFB, which is a negative regulator of RANKL-induced osteoclastogenesis. MCTO is an extremely rare autosomal dominant (AD) disorder that typically arises spontaneously and causes carpotarsal osteolysis, often followed by nephropathy. To the best of our knowledge, this is the first study reporting genetically diagnosed multicentric carpotarsal osteolysis syndrome in the Balkans.